Experimental study on dynamic response and residual mechanical behavior of SRC columns under repeated lateral impacts. (August 2022) - Zeng, Lei; Liu, Yanhua; Zhang, Heng; Mo, Jinxu; Liu, Changjun; Xiao, Yunfeng
Highlights: Repeated impact tests on axially-loaded SRC columns with built-in L-shaped steel were carried out. The residual mechanical properties after multiple impacts were preliminarily quantified. The dynamic response and quasi-static test results of SRC columns were analyzed. Abstract: The steel reinforced concrete(SRC) column is a key bearing part of some kinds of buildings and bridges, and its failure is usually the main cause of progressive structural collapse. To evaluate the column as-built performance, this paper reports the impact behavior of seven SRC columns with built-in L-shaped steels under out-of-plane lateral multiple impacts and the corresponding residual axial mechanical properties. The column is first subjected to three repeated impact loading under the same impact energy to study its impact resistance. Subsequently, the axial compression test is carried out to explore residual behavior. The influences of impact height, stirrup ratio and axial compression ratio on its performance are considered and discussed in detail. Results indicate that the column does not collapse or perforate after three times of impact, showing good impact resistance. Flexural-shear failure is the main failure mode under the first impact. And columns with large axial pressure gradually experience local punching failure from overall failure because the axial pressure inhibits the oblique crack. With the increase of impact times, the peak impact loads of the hammer reduced while the mid-span displacement of the specimen increased continuously. And the performance of column deteriorates sharply after two impact damages. The static tests showed that the residual axial bearing capacity was deeply influenced by the induced residual deformation. Both the impact behavior and residual mechanical properties were improved with the increase of stirrup ratio. In addition, the deformation of specimen after impact damage caused the constraint effect of stirrup in the initial stage of axial compression test, leading to the difference in the ascending stage of load displacement curves.